ダイ46ジ ニホン ナンキョク チイキ カンソクタイ エットウ ホウコク 2005-2006 - 渡邉, 研太郎; ワタナベ, ケンタロウ; Watanabe, Kentaro (2012)
P(論文) 第46 次日本南極地域観測越冬隊は37 名で構成され,全員が昭和基地で越冬した.2005 年2 月1 日から1 年間,第45 次越冬隊より基地運営を引き継ぎ,第VI期5 か年計画の4 年次にあたる観測・設営計画を実施して2006 年3 月28 日に全員無事に帰国した.例年より悪天候の日が多かったが,氷状も含め観測には大きな影響を及ぼさなかった.定常観測やモニタリング研究観測では着実にデータを取得し,プロジェクト研究観測では宙空圏,気水圏,地圏,生物圏の観測計画を実施した.ドームふじ基地での氷床深層掘削のため,中継拠点への燃料輸送を行い,7 名が10 月17 日から翌年2 月10 日までの内陸合同観測に加わった.一方,「昭和基地クリーンアップ4 か年計画」の2 年次として,使用済み雪上車18 台を回収し,廃棄物の持ち帰り目標量を超える205 t を集積した.広報では昭和基地と国内外の学校,科学館等をライブ映像で結び,「南極教室」を45 回開催するなど積極的に情報発信を行った. The wintering party of the 46th Japanese Antarctic Research Expedition (JARE-46) was consisted of 37 expedition personnel. All members overwintered at Syowa Station. It conducted the fourth year's research and logistical program in the VIth five-year plan of JARE for one year from February 1, 2005 taking over management of the station from JARE-45 and all the members returned home safely on March 28, 2006. There were more bad weather days than usual but neither they nor the sea ice condition affected research activities. Planned data were collected steadily by routine and monitoring observations. Plans of research observations of the atmosphere, hydrosphere, geosphere and biosphere were implemented. For deep ice coring at Dome Fuji Station, fuel wastransported to the relay point and seven members participated in an inland joint party from October 17 to February 10. As the second year of a four-year plan of a clean-up project for Syowa Station, 18 used snow vehicles were recovered and a total of 205 tons of waste, more than targeted, was collected for removal from Antarctica. JARE-46 was involved actively in an outreach program with "Antarctic classes" held 45 times, connecting Syowa Station and schools or science museums in Japan and the U.S.A. through live images. departmental bulletin paper